Velocity specificity of weight training for kayak sprint performance - Liow, D. K.; Hopkins, W. G. (Medicine & Science in Sports & Exercise, 2003)
Purpose: Athletes often use weight training to prepare for sprint events, but the effectiveness of different types of weight training for sprinting is unclear. We have therefore investigated the effect of slow and explosive weight training on kayak sprint performance. Methods: Twenty-seven male and 11 female experienced sprint kayakers were randomized to slow weight training, explosive weight training, or control (usual training) groups. Weight training consisted of two sessions per week for 6 wk; in each session the athletes performed 3-4 sets of two sport-specific exercises with a load of 80% 1-repetition-maximum. The two training programs differed only in the time taken to complete the concentric phase of the exercises: slow, 1.7 s; explosive, <0.85 s. To determine the effects of training on sprint acceleration and speed maintenance, the athletes performed 15-m kayaking sprints pre- and posttraining; an electronic timing system provided sprint times at 3.75-, 7.5-, and 15-m marks. Results: Relative to control, both types of weight training substantially improved strength and sprint performance. The improvements in mean sprint time over 15 m in each group were: slow, 3.4%; explosive, 2.3%; control, -0.2% (90% confidence limits for pairwise differences, approximately +/-1.4%). Over the first 3.75 m, the improvements were: slow, 7.1%; explosive, 3.2%; control, 1.4% ( approximately +/-2.6%). Over the last 7.5 m, the improvements were: slow, 2.1%; explosive, 3.0%; control, -0.8% ( approximately +/-1.9%). Conclusions: Slow weight training is likely to be more effective than explosive training for improving the acceleration phase of sprinting, when force is high throughout the length of the stroke. Explosive weight training may be more effective in speed maintenance, when forces are developed rapidly over a short period at the start of the stroke.